Transforming Capitalism through Real Utopias: A Critical Engagement. Issue 2 (November 2013) - McCabe, Conor
This article argues that Wright's work poorly understands the frameworks and organisational structures necessary to confront class power. Taking Wright's symbiotic strategies, it makes the point that if those strategies start to make gains, capital will react – and with force – but that Wright fails to build this into his argument. This leaves unaddressed the changes in class power in the past forty years and the implications of these for viable counter-capitalist strategies, avoiding any mention of trade unions or political parties. It states that the missing element in Wright's proposals is class power. Identifying financialisation as being at the heart of the changes in class power, it sees the state and state services as a crucial battleground as any democratic gains here are losses for finance capital. As the drive to dismantle the welfare state places more pressure on women, the article ends by focusing attention on the importance of women's struggles against cutbacks and privatisation of state provision.